Intraoperative Methadone Versus Non-Methadone Analgesia in Pediatric Cardiac Surgery: A Retrospective Cohort Study - Brian Blasiole; Danielle R. Lavage; Hsing-Hua Sylvia Lin; Scott E. Licata; Sahana Sivam; Inesh Sivam; Laura M. Le; Senthilkumar Sadhasivam (Children)
Introduction: Methadone is an opioid-sparing opioid and it is increasingly used in children undergoing surgery due to its beneficial effects on postoperative pain scores, decreased opioid requirements, and fewer adverse effects compared to other opioids. Intraoperative methadone is not well studied in pediatric cardiac surgery. We hypothesized that intraoperative methadone-based analgesia would provide comparable effectiveness in pain management to non-methadone-based analgesia, including caudal morphine, following pediatric cardiac surgery. Methods: We conducted a retrospective cohort study of 287 children undergoing cardiac surgery using single institutional electronic health records with Society of Thoracic Surgeons database outcomes. Patients were administered intravenous opioids plus caudal morphine (≤6 years) or intravenous opioids in the non-methadone group versus intravenous methadone (two 0.1 mg/kg doses given intraoperatively) with or without additional intraoperative opioids. The primary outcome was postoperative opioid use in morphine milligram equivalents (MME)/kg. Results: This study included 287 pediatric cardiac surgical patients with a mean age of 3.8 years, 59% male, and 72% White. Among 287 patients, 67 (23%) received intraoperative methadone. Unadjusted analysis showed the methadone group had lower postoperative opioid use on the day of surgery (median = 0.3 vs. 0.5 MME/kg, p = 0.005). Adjusted analyses showed there were no significant differences in postoperative opioid use, average pain, maximum pain, antiemetic use, reintubation, and use of naloxone between methadone and non-methadone groups. Hospital length of stay was 2.62 times longer (95% CI: [1.55, 4.41] p < 0.001) in the methadone group vs non-methadone group, but this was only shown in the younger children (≤6 years), who also had higher max pain scores in the methadone group. All outcomes were similar between analgesia groups in older children (>6 years). Conclusions: Intraoperative methadone-based analgesia had comparable effectiveness in postoperative opioid use, pain, and antiemetic use compared to non-methadone-based intraoperative pain management for pediatric cardiac surgery. Large prospective studies of perioperative methadone are needed to examine methadone’s analgesic benefits in children undergoing cardiac surgery.